Geographic Variation in Festuca rubra L. Ploidy Levels and Systemic Fungal Endophyte Frequencies ... : التباين الجغرافي في Festuca rubra L. مستويات الصبغية وترددات الفطريات الداخلية الجهازية ... - Serdar Dirihan; Marjo Helander; Henry Väre; Pedro E. Gundel; Lucas A. Garibaldi; J. Gonzalo N. Irisarri; Irma Saloniemi; Kari Saikkonen (OpenAlex, 2016)
Polyploidy and symbiotic Epichloë fungal endophytes are common and heritable characteristics that can facilitate environmental range expansion in grasses. Here we examined geographic patterns of polyploidy and the frequency of fungal endophyte colonized plants in 29 Festuca rubra L. populations from eight geographic sites across latitudes from Spain to northernmost Finland and Greenland. Ploidy seemed to be positively and negatively correlated with latitude and productivity, respectively. However, the correlations were nonlinear; 84% of the plants were hexaploids (2n = 6x = 42), and the positive correlation between ploidy level and latitude is the result of only four populations skewing the data. In the southernmost end of the gradient 86% of the plants were tetraploids (2n = 4x = 28), whereas in the northernmost end of the gradient one population had only octoploid plants (2n = 8x = 56). Endophytes were detected in 22 out of the 29 populations. Endophyte frequencies varied among geographic sites, and ... : تعدد الصيغ الصبغية والنباتات الفطرية التكافلية Epichloë هي خصائص شائعة وموروثة يمكن أن تسهل توسع النطاق البيئي في الأعشاب. درسنا هنا الأنماط الجغرافية لتعدد الصيغ الصبغية وتواتر النباتات المستوطنة الفطرية في 29 مجموعة من سكان فيستوكا روبرا ل. من ثمانية مواقع جغرافية عبر خطوط العرض من إسبانيا إلى أقصى شمال فنلندا وغرينلاند. بدا أن الصبغة الصبغية مرتبطة بشكل إيجابي وسلبي بخط العرض والإنتاجية، على التوالي. ومع ذلك، كانت الارتباطات غير خطية ؛ 84 ٪ من النباتات كانت سداسية الصيغة الصبغية (2n = 6x = 42)، والارتباط الإيجابي بين مستوى الصبغيات وخط العرض هو نتيجة لأربعة تجمعات فقط تشوه البيانات. في الطرف الجنوبي من التدرج، كانت 86 ٪ من النباتات رباعية الصيغة الصبغية (2n = 4x = 28)، بينما في الطرف الشمالي من التدرج، كان لدى مجموعة واحدة فقط نباتات ثماني الصيغة الصبغية (2n = 8x = 56). تم اكتشاف النابتات الداخلية في 22 من أصل 29 مجموعة سكانية. اختلفت ترددات النباتات الداخلية بين المواقع الجغرافية والسكان والموائل داخل المواقع الجغرافية بغض النظر عن الصبغة أو خط العرض أو الإنتاجية. تم العثور على أعلى ترددات شاملة للنباتات ...